Lrp4 domains differentially regulate limb/brain development and synaptic plasticity. - Theresa Pohlkamp; Murat Durakoglugil; Courtney Lane-Donovan; Xunde Xian; Eric B Johnson; Robert E Hammer; Joachim Herz (PLoS ONE, 2015)
Apolipoprotein E (ApoE) genotype is the strongest predictor of Alzheimer's Disease (AD) risk. ApoE is a cholesterol transport protein that binds to members of the Low-Density Lipoprotein (LDL) Receptor family, which includes LDL Receptor Related Protein 4 (Lrp4). Lrp4, together with one of its ligands Agrin and its co-receptors Muscle Specific Kinase (MuSK) and Amyloid Precursor Protein (APP), regulates neuromuscular junction (NMJ) formation. All four proteins are also expressed in the adult brain, and APP, MuSK, and Agrin are required for normal synapse function in the CNS. Here, we show that Lrp4 is also required for normal hippocampal plasticity. In contrast to the closely related Lrp8/Apoer2, the intracellular domain of Lrp4 does not appear to be necessary for normal expression and maintenance of long-term potentiation at central synapses or for the formation and maintenance of peripheral NMJs. However, it does play a role in limb development.